2022
DOI: 10.31223/x52h1k
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

The Mechanisms of Tsunami Amplification and the Earthquake Source of the 2021 M7 Acapulco, Mexico, Earthquake

Abstract: Here we show a slip model for the 2021 M7 Acapulco, Mexico, earthquake produced by inversion of strong motion, GNSS, tide gauge, and InSAR data. The earthquake occurs within the Guerrero gap, identified as a region of concern for its seismogenic potential and paucity of large events. We find that rupture was compact, constrained to depths between 10 and 20 km and consistent of two main slip patches. The slip model leaves a broad swath of the megathrust unbroken. Whether the event signals a reactivation of larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 35 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…The slip model of the 2021 event was also determined by Melgar et al (2022) using strong motion, GNSS, tide gauge, and InSAR data. In the slip model determined by Melgar et al (2022), two maximum slip zones are observed: a zone of maximum slip in the downdip portion of the rupture zone and another in the updip part.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The slip model of the 2021 event was also determined by Melgar et al (2022) using strong motion, GNSS, tide gauge, and InSAR data. In the slip model determined by Melgar et al (2022), two maximum slip zones are observed: a zone of maximum slip in the downdip portion of the rupture zone and another in the updip part.…”
Section: Discussionmentioning
confidence: 99%
“…The slip model of the 2021 event was also determined by Melgar et al (2022) using strong motion, GNSS, tide gauge, and InSAR data. In the slip model determined by Melgar et al (2022), two maximum slip zones are observed: a zone of maximum slip in the downdip portion of the rupture zone and another in the updip part. In the model determined in this study, a zone of maximum slip is observed in the downdip zone and slip corresponding to approximately 20% of the maximum slip is observed in the updip area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations